PD-1 expression on peripheral blood CD4+ T lymphocytes in treatment-naïve HNSCC patients: a flow cytometry analysis - Godara, Jatin; Agarwal, Arti; Kaur, Beant; Kumar, Manish (International Journal of Research in Medical Sciences, 2025)
Background: Head and neck squamous cell carcinoma (HNSCC) is a globally prevalent malignancy with a high burden in India. Programmed death protein-1 (PD-1), an immune checkpoint receptor, is a potential biomarker in several cancers. However, its prognostic relevance on circulating CD4+ T cells in HNSCC remains uncertain. To evaluate PD-1 expression on peripheral blood CD4+ T lymphocytes in treatment-naïve HNSCC patients and determine its association with clinicopathological features. Methods: This prospective, cross-sectional study included 32 histopathologically confirmed, treatment-naïve HNSCC patients at a tertiary care center over 18 months. Peripheral blood mononuclear cells were analyzed using flow cytometry (Cytomics FC 500, Beckman Coulter) with antibodies against CD3, CD4 and PD-1 (CD279). PD-1 expression was quantified on gated CD4+ T cells. Statistical analysis was performed using SPSS v25.0, with significance set at p<0.05. Results: The mean age was 49.94±10.5 years; all patients were male. The most common tumor sites were palate (40.63%), tongue (31.25%) and oral mucosa (28.13%). The mean PD-1 expression on CD4+ T lymphocytes was 5.51±2.06%. PD-1 expression showed no statistically significant association with tumor site (p=0.843), histological differentiation (p=0.363), lymph node metastasis (p=0.930) or tumor stage (p=0.930). Conclusions: PD-1 expression on peripheral CD4+ T cells does not correlate with tumor site, grade, stage or metastatic status in HNSCC patients. While flow cytometric quantification of PD-1 may offer non-invasive insights, its standalone utility as a prognostic marker in peripheral blood appears limited. Larger studies incorporating tumor microenvironment analysis and longitudinal follow-up are warranted.